Proposition of Thermal-Diffusion-Induced Spiral Model for the Rapid Oil-Film Breakdown Process during Scuffing - Mamoru Tohyama (Japanese Society of Tribologists, 2021)
The dominant factors and processes for the rapid progression of scuffing from a partial area to an entire surface under lubricated, plane contact, and pure sliding conditions were studied by performing an in situ observation of the surface, and in situ measurements of the oil-film thickness and temperature distributions during scuffing. Transitions of the oil-film thickness were measured using three-wavelength optical interferometry, and the temperature distributions of the sliding surface were measured using thermography. It was observed that oil-film breakdown progressed from a partial area to an entire surface within several tens of milliseconds under high sliding speed and high-load conditions. The proposed process of the rapid progression of oil-film breakdown on the surface was described using the "thermal-diffusion-induced spiral model." The processes in the model are as follows: (I) the frictional heat generated in a solid contact area diffused into the adjacent region of the surface; (II) the oil-film temperature in the adjacent region increased within a short time, as the films were very thin (several tens of nanometers); (III) the viscosities of the oil-films decreased; (IV) the solid contact area grew larger, and these phenomena repeated continuously until the oil-film breakdown reached the entire surface.